Profil Siswa Agresif dan Peranan Guru BK - Hidayat, Hafiz; Yusri, Yusri; Ilyas, Asmidir (Konselor, 2013)
Abstract: Teens have a positive and negative behavior. Negative behavior is not characteristic of normal adolescent development, adolescents are developing will exhibit positive behavior. One of the teens indicated negative behavior is aggressive behavior. It can be seen in SMA N 5 Padang is quarrelsome, like teasing, hitting, pinching her, saying rude, insulting. This study aimed to describe the type of aggressive behavior of students and the role of BK teachers to address students' aggressive behavior SMAN 5 Padang. This study used a descriptive approach. The study population was a high school student Padang N 5 340 people with a total sample amounted to 77 people. Questionnaire data collection techniques to use. Data were analyzed using Microsoft Office Excel 2007. The findings showed that students' views of the aggressive actions hurt people physically with a percentage of 35.32%, while the aggressive actions of the student views of hurting people verbally 41.30% and aggression seen from damaging and destroying property by 30 percent, 42%. This means that the presence of aggressive behavior in SMA N 5 Padang.Â